TANGGUNG JAWAB PENJUAL KEPADA PEMBELI MELALUI MEDIA ONLINE MENURUT UNDANG UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK PADA TOKO ONLINE RYNAKOSMETIK - Rachman, M. Yogi; Hanifah, Mardalena; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Since the internet was first introduced it never suspect that impact is more intense. Internet bring the world economy enters a new phase like trading via internet. Indonesia through legislation Nomor 11 tahun 2008 Tentang Informasi dan Transaksi Elektronik regulating the trade via the internet, like sale and purchase agreement. Sale and purchase agreement via the internet is considered to have a high risk because of the difficulty in reaching the parties to a tort action in the transaction. Therefore it necessary legal protection and legal certainty for legislation yet not accommodate, thus should be pursued to achieve a balance of law remain in these conditions.The purpose of this thesis, as: first, to determine the legal protection of the parties in the implementation of the agreement via internet. Second, to determine the inhibiting factors in the purchase agreement via internet.This kind of research can be classified in sociological juridical research, because it done by analyzing data in laws and compare with the facts obtained through interviews. Overall population and sample related to the issues examined in this study, the data source used primary data, secondary data and tertiary data, collection data techiniques in this study with interviews and literature study.Of the research problem, there are two main things that can be concluded. First, legal protection for consumen in the purchase agreement via internet, including protection laws agreed upon by both parties as well as on electronic evidence set forth in pasal 5 ayat 1 Nomor 11 tahun 2008 Tentang Informasi dan Transaksi Elektronik. Second, inhibiting factor in internet transactions specifically the barriers, obstacle due the distance, space and time, the general of obstacle, data authenticity of obstacle, the presence of items and in proving the prowerss of the parties. Advice author, first, users expect buyers in particular need to be more cautious in making transactions via internet, buyers should also be carefully and thoroughly to avoid losses due to the irresponsible parties. Second, it should be the user in transactions via internet, especially sellers must guarantess goods and good faith also didn’t escape responsibility in trade through via internet.Keywords : Responsibility, Sale and purchase agreement, electronic media